Weed management in azuki bean with preplant incorporated herbicides. Issue 1 (2nd December 2020) - Soltani, Nader; Brown, Lynette; Sikkema, Peter H.
Abstract: There are only two soil‐applied herbicides, pendimethalin and imazethapyr, registered for weed management in azuki bean production in Ontario, Canada. Three experiments were completed in Ontario over three consecutive years (2017, 2018, and 2019) to develop weed management programs in azuki bean with various preplant incorporated (PPI) herbicides. There was up to 6% azuki bean injury with the herbicide treatments evaluated. Pendimethalin + S ‐metolachlor controlled redroot pigweed, common lambsquarters, barnyard grass, and green foxtail at ≥99% but provided poor control of common ragweed and wild mustard. The two‐way mixtures of pendimethalin + imazethapyr and pendimethalin + halosulfuron, and the three‐way mixtures of pendimethalin + S ‐metolachlor + imazethapyr and pendimethalin + S ‐metolachlor + halosulfuron controlled redroot pigweed, common lambsquarters, wild mustard, barnyard grass, and green foxtail at ≥99% and common ragweed at >73%. Common ragweed control was consistently higher with tankmixes that contained halosulfuron. Metribuzin controlled redroot pigweed, common ragweed, common lambsquarters, wild mustard, barnyard grass, and green foxtail at >93%, 88%, 99%, 97%, 68%, and 50%, respectively. Weed density and aboveground biomass reductions were similar to those of weed control. Weed presence reduced azuki bean yield by 83%. Reduced weed presence with the herbicide treatments assessed resulted in azuki bean yield that was similar to that of the weed‐free control with the exception of pendimethalin, halosulfuron, and metribuzin (low rate); weed interference with the aforementioned herbicides decreased azuki bean yield by 50%, 56%, and 44%, respectively. Based on these results, pendimethalin, S ‐metolachlor, halosulfuron, and imazethapyr applied PPI, applied alone, or in a two‐way or three‐way tankmixture can be used safely for the control of common annual grass and broadleaf weeds in Ontario, Canada.